Union of the Comoros : Interim Poverty Reduction Strategy Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
The Union of the Comoros's Interim Poverty Reduction Strategy (PRGS) paper reports that the government's macroeconomic objectives under the PRGS framework entail preserving major economic equilibria. To increase control over government spending, the government intends to reduce the relative weight of the wage bill, manage the public debt efficiently, and rationalize government outlays. Reforms are under way, with World Bank support aimed at more efficient handling of the public debt and improving the quality of services provided in the context of a rehabilitation of public finance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet